K fclin,fmsr Qclin,Qmsr CORRECTION FACTORS OF PLASTIC SCINTILLATORS AND OTHER STEREOTACTIC DETECTORS FOR SUB-CENTIMETER PHOTON FIELDS USING MONTE CARLO (2017)
The goals of this work are:  (1)  To  evaluate  a  plastic scintillation detector and other stereotactic dosimeters for measuring output factors,  dose  profiles  and  percent  depth dose  curves  of  small  and  sub-centimeter  radiation  fieldsand  (2)  to  obtain  tables  of K fclin,fmsr Qclin,Qmsr correction  factors based  on  Monte  Carlo  simulations  using  codes BEAMnrc and DOSXYZnrc.Tables of output ratios and dose profiles for radiation fields conformed by a micro-multileaf collimator were obtained for the stereotactic detectors: 1) Standard Imaging W1 Exradin Plastic Scintillation Detector with 1 mm diameter and 3 mm length, 2) PTW dosimetry diode E type 60017 with 1.13 mm diameter and 30 µm thickness and 3) PTW Pinpoint 31016 3D ionization chamber with 3.13 mm diameter.Monte Carlo BEAMnrc simulations were performed for the      6 MeV energy of a Varian  Clinac iX linear accelerator with   the  micro-multileaf  collimator  attached  to  its  gantry. The OSXYZnrc Monte Carlo code was used to calculate the output factors Ωfclin,fmsr Qclin, Qmsr ,water MC and the dose profiles in a virtual water phantom by means of the phase space file obtained  from  the  BEAMnrc  simulation.  The K fclin,fmsr Qclin,Qmsr factor tables presented in this work show that for field sizes with radius larger than the range of secondary charged particles, the corrections  for  the  set  of  detectors  are  lower than 7 % compared with Monte Carlo calculations. However, for sub-centimeter radiation fields, the corrections are about    of  23 %  for  the  PTW  Pinpoint  ionization  chamber  and  up to 12 % for the rest of detectors.